Wettability at high temperatures - Eustathopoulos, Nicolas (Pergamon materials series ;, 1999)
The purpose of this book is to bring together current scientific understanding of wetting behaviour that has been gained from theoretical models and quantitative experimental observations. The materials considered are liquid metals or inorganic glasses in contact with solid metals or ceramics at temperatures of 200-2000 o C. Wetting has been a significant scientific concern for the last two centuries and reference will be made to classical work by nineteenth century scientists such as Dupre, Laplace and Young that was validated by observations of the behaviour of chemically inert ambien.